(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article analyzes the clinical and pathogenetic course of recurrent bronchitis in children against the background of comorbid diseases. Also, the mechanism of development, diagnosis and treatment methods are discussed in this case.